The Impact of Instagram account @visitbogor and uploads of nature tourism photos towards the Visiting Interests of Its Followers (Empirical Study on Visit Interests in natural tourism of Bogor city) - Nuri Ayu Anjani; Eko Hartanto (2020)
This research is conducted with the aim of knowing the impact of the Instagram account @visitbogor to the interest in visiting the followers, knowing the effects of uploading natural travel photos on a visiting interest of followers, knowing the impact of Instagram account @visitbogor and uploading of natural travel photos to the interest of visiting followers. This research samples a total of 400 respondents with purposive sampling techniques filtered on the basis of certain criteria. The study uses the S-O-R theory. The data analysis methods in this study used multiple linear regression analyses and hypothesis testing using the T test and F test with the help of SPSS version 22. Acquired regression coefficient value Y = 2.160 + 0.163 X1 + 0.720 X2, relationship level correlation value is said to be strong because it exists at a 0.60-0,799 interval of 0.730 with a percentage of 73% coefficient of determination value of 0.533 which means that 53.3% of visiting interest in followers is influenced by the Instagram account is presented @visitbogor and upload of nature tourism photos with H1 received based on the results of Thitung (2.195) Ttabel (1.966) on a 0.05. H2 received according to Thitung (20.230) Ttabel (1.966) on sig Î± = 5% with sig value of 0.000 0.05. H3 is received based on the result of Fcalculate (226.196) Ftabel (3.86) on a sig Î± = 5% with a sig value of 0.000 0.05. The results showed a significant influence between the variables of the Instagram account's cast @visitbogor and the uploading of natural tourist photos of the followers ' visiting interests.